Influence Lifestyle, Consumer Ethnocentrism, Product Quality on Purchase Decision through Purchase Intention - Amri, Sirly; Prihandono, Dorojatun (Universitas Negeri Semarang, 2019)
The basic marketing strategy of a company is studying consumer behavior include consumer decision-making process. Before the advent of consumer purchasing decisions has an interest first. This study aimed to examine the direct and indirect effects of lifestyle, consumer ethnocentrism, product quality, and purchase intention as an intervening variable in the purchase decision. The population this research that consumers Batik Unggul Jaya in Kota Pekalongan. The total sample of 116 respondents with purposive sampling technique through a Likert scale questionnaire. Analysis of data using descriptive percentage and path analysis, The results showed that lifestyle has a significant positive effect on purchase decision, customers ethnocentrism has a significant positive effect on purchase decision, product quality has a significant positive effect on purchase decision, and purchase intention have a significant positive effect on purchase decision, as well as the mediating influence of lifestyle, consumer ethnocentrism, and product quality of the purchase decision.